Mitral atresia with transposed great arteries and normal semilunar valves: a rare combination. (23rd September 2015) - Rajesh, Gopalan Nair; Mohanan, Sandeep; Vellani, Haridasan
Abstract: Mitral atresia is commonly seen as a part of the spectrum of hypoplastic left heart syndrome, and it is usually associated with multiple levels of systemic outflow tract obstruction. Isolated mitral atresia with a normal aortic valve is extremely rare. We report the rare combination of mitral atresia, transposition of the great arteries, and unobstructed systemic and pulmonary blood flow.